Pomen pouka književnosti v gimnazijskem programu - Ambrož, Darinka (Jezik in slovstvo, 2019)
The paper addresses the importance of teaching literature in times when many pupils are less attracted to reading or consider it to be too demanding, as their worlds of words are being replaced by worlds of images. The author nonetheless advocates Confucius's idea about the great importance of learning poems.
Keywords: bralni užitek; gimnazije; književnost; literarna klasika; pomen branja; pouk književnosti; sporazumevalne zmožnosti; šolski kurikulum; učni načrt